"Fake Smile. Everything is under Control.": The Flawless Performance of Motherhood. Issue 1 (1st January 2021) - DeGroot, Jocelyn M.; Vik, Tennley A.
Abstract : As mothers engage in domestic responsibilities, one task they encounter is maintaining face in public spaces, on and offline. One hundred thirty-six mothers completed an open-ended online survey, and the data were coded using inductive thematic analysis. Results indicate that mothers feel the intense burden of performing motherhood flawlessly on and offline as they project a positive self-image, avoid sharing challenges, and discuss only positive experiences online, leading to the perception of living separate front and backstage lives. Some of the social constructions are toxic for mothers and motherhood yet are reinforced by other mothers in the everyday performance of motherhood. These findings advance Goffman's Dramaturgy as well as our understandings of the pressure mothers feel to present and maintain a perfect enactment of motherhood.